Ismail al Faruqi: the link between Tudor and the Muslim world - Ali Yusuf, Imtiaz Ahmed Shaukat (iPub Global Connection, LLC, 2019)
Al Faruqi brought a comprehensive and blended approach that combined a rationalist approach to monotheism which was both modernist and activist, along an impartial path to the study of religion. In a way, he was a modern successor to the medieval Muslim scholars of comparative religion such as al-Biruni (973-1048 CE) and al-Shahrastani (1086-11-53 CE),